Risk Factors of Hypoperfusion on MRI of Ischemic Stroke Patients Within 7 Days of Onset - Xiao, Jingjing; Liang, Huazheng; Wang, Yue; Wang, Shaoshi; Wang, Yi; Bi, Yong (Frontiers in Neurology, 2021)
Objective: Hypoperfusion is an important factor determining the prognosis of ischemic stroke patients. The present study aimed to investigate possible predictors of hypoperfusion on MRI of ischemic stroke patients within 7 days of stroke onset. Methods: Ischemic stroke patients, admitted to the comprehensive Stroke Center of Shanghai Fourth People's Hospital affiliated to Tongji University within 7 days of onset between January 2016 and June 2017, were recruited to the present study. Magnetic resonance imaging (MRI), including both diffusion-weighted imaging (DWI) and perfusion-weighted imaging (PWI), was performed within 7 days of the symptom onset. Time to maximum of the residue function (Tmax) maps were automatically evaluated using the RAPID software. The volume of hypoperfusion was measured outside the infarct area based on ADC < 620 × 10−6 mm2/s. The 90 d mRS score was assessed through either clinic visits or telephone calls. Multivariate step-wise analysis was used to assess the correlation between MR findings and clinical variables, including the demographic information, cardio-metabolic characteristics, and functional outcomes. Results: Among 635 patients admitted due to acute ischemic stroke within 7 days of onset, 241 met the inclusion criteria. Hypoperfusion volume of 38 ml was the best cut-off value for predicting poor prognosis of patients with cerebral infarction (90 d-mRS score ≥ 2). The incidences of MR perfusion Tmax > 4–6 s maps with a volume of 0–38 mL or >38 mL were 51.9% (125/241) and 48.1% (116/241), respectively. Prior stroke and vascular stenosis (≥70%) were associated with MR hypoperfusion. Multivariate step-wise analysis showed that prior stroke and vascular stenosis (≥70%) were risk factors of Tmax > 4–6 s maps, and the odds ratios (OR) were 3.418 (adjusted OR 95% CI: 1.537–7.600), and 2.265 (adjusted OR, 95% CI: 1.199–4.278), respectively. Conclusion: Our results suggest that prior stroke and vascular stenosis (≥70%) are strong predictors of hypoperfusion in patients with acute ischemic stroke within 7 days of stroke onset.